Identity Through Distinction: Contextualizing Populist In- and Outgroup References - Lisa Zehnter (Political Studies, 2025)
People-centrism is a key defining characteristic of the dominant ideational approach to populism. Yet, who do populist actors consider their ingroup? Research on the empirical characteristics of who is deemed “the people” is scarce. Bringing together previous work on populism, group references, and social identity theory, this article develops a typology of populist in- and outgroup references. Applying word embeddings, a novel text-as-data approach, the empirical characteristics of these groups are identified and contextualized in election manifestos from Austria, Germany, and Switzerland between 1983 and 2021. In line with the theoretical expectations, the results show that the ingroups' identity remains imprecise and is primarily constructed indirectly, namely through opposition to and in distinction from the outgroup. Right-wing populist parties can be distinguished from other parties through their negative references to outgroups such as foreigners or Muslims . These references indirectly create the ingroup ex negativo . These findings have implications for the representation of minority groups and political polarization in liberal democracies.
Keywords: 300; group references; people-centrism; populism; word embeddings